COLLECTIVE INVESTMENT SCHEMES’ RETURNS AND ONE YEAR COVID-19 EXPERIENCE: THE NIGERIA’S CASE - Gbenga Festus Babarinde; Bashir Ahmad Daneji (Universitas Kuningan, 2021)
This study examines the impact and nexus between cases of coronavirus disease (COVID-19) and the returns of seven classes of collective investment schemes (CIS) in Nigeria (bond funds, equity-based funds, fixed income funds, ethical funds, money market funds, mixed funds and real estate funds) within the first 52 weeks of the outbreak of the pandemic in Nigeria, 27th February, 2020 to 26th February, 2021 using Auto-regressive Distributed Lag and Pearson correlation techniques. Empirical findings suggest that COVID-19 cases and returns of collective investment schemes in Nigeria are cointegrated while COVID-19 cases are negatively correlated with the returns from bonds funds, equity based funds and money market funds as against the positive correlation between COVID-19 cases and returns from ethical, fixed income and real estate funds. Furthermore, COVID-19 confirmed cases are negatively related with returns from mixed fund as against the fund’s returns’ positive correlation with COVID-19 fatal and discharged cases. Moreover, except for COVID-19 discharged cases which has significant positive impact on fixed income funds’ returns, none of the other indicators of COVID-19 exerts significant influence on the returns of each of the seven CIS in Nigeria. It can be concluded that COVID-19 cases do not have significant impact on collective investment schemes’ returns in Nigeria. It is recommended that collective investment schemes in Nigeria should be accorded the popularization, incentives, boost, empowerment it deserves by the government and the organized private sector. KEYWORDS: ARDL; COVID-19; Collective Investment Schemes; Returns; Mutual funds. JEL CLASSIFICATION: E44, G11, G14